Confirmation of Five Factors That Affect Temper Tantrums In Preschool Children: A Literature Review - Umami, Desi Aulia; Sari, Lezi Yovita (Journal of Global Research in Public Health, 2020)
Temper Tantrum can cause aggressive behavior that endangers the child and the people in their environment, makes the child feel inferior, curses, injures, and even causes death. The research objective is to determine the effect of family environment, parenting, self-adjustment, children's independence and emotional intelligence on the temper tantrums of preschool children. The research design used cross sectional. The results showed that the variable Temper Tantrum of preschool children was directly influenced by the family environment 29.8%, 22% parenting style, 8.68% adjustment, 4.53% children's independence, 7.06% emotional intelligence. While the direct effect of the family environment on self-adjustment is 44.7%, adjustment to emotional intelligence is 13.72%, parenting styles for self-adjustment are 3.61%, parenting styles for self-sufficiency 16.15%, family environment on independence 67.55% of children, parenting patterns of emotional intelligence 7.87%, family environment to emotional intelligence 54.49%, family environment to parenting 66.12% of parents, independence of children to adjustment 10.11% with Thus it was concluded that the family environment most influenced the temper tantrums of preschool children at RW 02, because the family environment was the child's first medium in socializing. Suggestions for children's independence and parenting styles for parents should give new enthusiasm for the activities given as well as for the children's achievements, achievements or efforts in realizing certain goals, which can be in the form of giving numbers or values, gifts, praise and awards, establishing good communication between children and parents.